ANALISIS PERBANDINGAN EFISIENSI PRODUKSI PADI SAWAH SISTEM TANAM JAJAR LEGOWO DAN SISTEM TANAM KONENSIONAL DI KABUPATEN KAMPAR - Ummi Noviqah Zarliyanti; Syaiful Hadi; Novia Dewi (UIR Press, 2021)
This study aims to analyze tecnically the cultivation of paddy jajar legowo planting systems and conventional planting systems, to analyze of farming and production efficency and to compare the effiinecy of the production of jajar legowo planting systems and conventional planting systems. This study was conducted by survey method and determination of the sample was carried out by multistage sampling with 72 respondents of lawland rice farmers in Kampar Regency. Analysis data used desriptive analysis, farm analysis, DEA (Data Envelopment Analysis), and independent samples t test analysis. The result of the study showed that technically the pady cultivaiton with the standart that was given by expert. For farming, the paddy of jajar legowo planitng systems has an RCR 0f 1,60 and a conventional planting systems of 1,31. Technical, allocative and economic efficeincy of lawland paddy with jajar legowo planting systems and convenitonal planting systems had no significantly different.